An evaluation of neurocognitive models of theory of mind - Schurz, Matthias; Perner, Josef (Frontiers in Psychology, 2015)
We review ten current neurocognitive theories of how Theory of Mind (ToM) is implemented in the brain and evaluate them based on the results from a recent meta-analysis by Schurz et al. (2014), where they distinguished between six types of ToM tasks identified as the most frequently used in imaging research on ToM. From existing theories about cognitive processes being associated with certain brain areas, we deduce predictions about which areas should be engaged by the different types of ToM tasks. We then compare these predictions with the observed activations in the meta-analysis, and identify a number of unexplained findings in current theories. These can be used to revise and improve future neurocognitive accounts of ToM.